Model Of Technology Acceptance Affecting User Behavioural Intention In E-procurement Adoption In The Nigerian Public Sector - Musa, Usman (2023)
Electronic procurement (e-procurement) adoption has the potential to have a wide range of strategic, operational, and tactical benefits. E-procurement is viewed as a vehicle for improving public services and, as a result, has been in the forefront of public procurement reform in many nations. Despite all the efforts by the Nigerian government to adopt e-procurement in the country, the adoption of e-procurement technology is very low in the public sector. This has been attributed to the lack of existing model for e-procurement adoption and lack of e-procurement training possessed by the public sector procurement employees. Also, there is absence of studies exploring the factors that affects user intention to adopt e-procurement in the Nigerian public sector. This study aims to develop a technology acceptance model that affects user behavioural intention to adopt e-procurement in the Nigerian public sector taking in to account the moderating role of training. The Technology Acceptance Model (TAM) model was adopted and extended with system related; security related; and personal psychology related technology factors. The survey research method was used to collect data using online questionnaire. A non-probability sampling technique and a simple random sampling were used to select 15 federal ministries and 278 respondents respectively for the data collection. The data were analyzed using the partial least square structural equation modelling technique. The results indicate that all the technology factors studied have significant effects on behavioural intention to adopt e-procurement except perceived ease of use, perceived compatibility and perceived risk